Plasma VWF: Ag levels predict long-term clinical outcomes in patients with acute myocardial infarction - Xier, Zulipiyemu; Zhu, Yu-Xia; Tang, Shou-Wei; Kong, Can; Aili, Dilihumaer; Huojia, Guzailinuer; Peng, Hui (Frontiers in Cardiovascular Medicine, 2023)
Background: A vital role in coronary artery disease is played by Von Willebrand factor (VWF), which serves as a bridge between platelets and the subendothelial matrix after vessel damage.The purpose of the study was to assess the validity of plasma VWF antigen (VWF:Ag) levels as a predictor of clinical outcomes after acute myocardial infarction (AMI). Methods: Three hundred and seventy-four patients were studied following coronary angiography, including 209 patients suffering from acute myocardial infarction and 165 healthy participants. Coronary angiography was followed by measurement of plasma VWF:Ag levels. Over a 2-year follow-up period, major adverse cardiopulmonary and cerebrovascular events (MACEs) were the primary endpoint. All-cause mortality was investigated as a secondary endpoint. Results: When compared to controls, patients with AMI had mean plasma VWF:Ag levels that were approximately 1.63 times higher (0.860±0.309 IU/mL vs. 0.529±0.258 IU/mL; P<0.001). The plasma VWF:Ag levels were substantially higher in patients who experienced MACEs after myocardial infarction vs. those without MACEs (1.088±0.253 IU/mL vs. 0.731±0.252 IU/mL; P<0.001). For predicting long-term MACEs using the optimal cut-off value (0.7884 IU/mL) of VWF:Ag, ROC curve area for VWF:Ag was 0.847, with a sensitivity of 87.2% and a specificity of 66.3% (95% CI: 0.792-0.902; P=0.001). Two-year follow-up revealed a strong link between higher plasma VWF levels and long-term MACEs. At the two-year follow-up, multivariate regression analysis revealed an independent relationship between plasma VWF:Ag levels and MACEs (HR=6.004, 95%CI:2.987-12.070). Conclusions: We found evidence that plasma VWF:Ag levels were independent risk factors for AMI. Meanwhile, higher plasma VWF:Ag levels are associated with long-term MACEs in people with AMI.